Biological effect of calcium and vitamin D dietary supplements against osteoporosis in ovariectomized rats - Mustafa, Reham A.; Alfky, Nehal A.A.; Hijazi, Haifa H.; Header, Eslam A.; Azzeh, Firas S. (Progress in Nutrition, 2018)
There is a direct association between the lack of estrogen and the progress of osteoporosis. This study was done to evaluate the biological effect of diet supplementation with calcium (Ca), and vitamin D (VD) on osteoporosis in ovariectomized (OVX) rats and to examine the possible potential mechanisms. Twenty-eight rats were randomly divided into 4 equal groups (n=7). To induce estrogen deficiency in rats, bilateral ovariectomy and sham (SHAM; negative control) surgery were done. In the basal diet, Ca and VD was supplemented with 210 mg/kg and 600 IU/kg, respectively, for 6 weeks. Alendronate as a standard anti-osteoporotic drug was used in a single weekly dose (3 mg/kg) for 6 weeks. After six weeks, serum markers of osteoporosis and bone femur status were evaluated. The results exposed that Ca and VD supplementation increased the body weight gain and diminished the uterine weight as a result of ovariectomy operation. These supplements significantly raised the serum Ca, bone-specific alkaline phosphatase, free thyroxin, and osteocalcin in OVX-rats, while the serum interleukin-1beta, interleukin-6, parathormone, and pyridinoline levels were significantly dropped. There were also significantly improved in femur bone mineral density and bone ash contents, mainly Ca and phosphorous. In conclusion, feeding of Ca and VD dietary supplements have an anti-osteoporotic activity in OVX rats due to improvement of bone formation and abolition of bone loss. The study recommends that intake of Ca and VD together may be beneficial for the inhibition of osteoporosis in postmenopausal women due to estrogen deficiency.